“Charged Humor” in der Stand-up Comedy von Migrant:innen in Wien - Jakiša , Miranda (Wiener Slawistischer Almanach, 2025)
This paper reviews the notion of “charged” (Krefting 2014: 2) or “risky” (Kotthoff 2010b) humor in contemporary stand-up ethno-comedy of South Slavs in Austria. I argue that the chargedness of ‘ethnic’ jokes is disappearing from recent forms of ethno-comedy due to the increasing influence of TikTok and Instagram. Instead, audiences of “charged humor” perceive themselves united in post-migrant “affective publics” (Papacharissi 2015).